IMPROVEMENT OF THE STEEL SMELTING CONTROL SYSTEM «MASTER» - Kharchenko Аlеxander; Lichkonenko , Natali; Kovalyov , Vitaliy; Lyashenko , Roman (Scientific Journal "Metallurgy", 2020)
In the open-hearth workshop of PJSC Zaporizhstal, a set of works have been carried out to improve the control system of the steelmaking production “Master”, which was originally designed to optimize deoxidation and alloying of steel at the outlet from the furnace into the ladle and for maintaining an electronic journal of express analysis of the chemical composition of liquid steel. The system has been added with: the function of controlling the quantity and quality of pig iron supplied to each heat; real-time melting parameters monitoring module with an operational forecast on the temperature of the liquid metal and the carbon content in it starting from heating and ending with the release from the furnace. A thermodynamic model of a steelmaking bath has been developed, including the metal, slag and gas phases, which allows predicting the main melting parameters before the actual temperature measurements and express metal analyzes begin, and then adjusting the predicted trajectories according to the actual measurements. A scheme was developed for the interaction of a steelmaking bath with a high-temperature reaction zone around a jet of injected oxygen. The algorithm for solving the problem of optimizing deoxidation-alloying of steel at the outlet from the furnace has been improved. The list of available materials for alloying has been expanded, materials for melting blending - molten iron, scrap, lime, limestone have been added. A real-time melting parameters monitoring module has been launched with an operational forecast on the temperature of the liquid metal and the carbon content in it starting from warming up and ending with the release from the furnace. The resolution of updating form data can vary and defaults to 30 s. For each melting period (heating, casting, melting, lapping, finishing), restrictive zones for oxygen consumption are displayed in accordance with the technological maps, forecast and actual measurements of the metal temperature, forecast and actual measurements of the carbon content in the metal, instantaneous oxygen and natural consumption gas on the tuyeres, positional sensor data on the position of oxygen tuyeres.